Efektivitas Media Pembelajaran Kahoot! dalam Mengukur Pemahaman Konsep Suhu dan Kalor - Tutik Yuliatun; Kristina Uskenat; Selestina Kostaria Jua (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
This study aims to determine the effectiveness of kahoot! learning media. in measuring the understanding of the concept of temperature and heat. The subjects of this study were 33 class VII students of MTs Al Ikhlas. The research model used is descriptive quantitative with the test instrument used in this study, namely 9 multiple choice questions with 4 answer options. The results of the analysis in this study showed that of the nine items, there were 1 item in the very good category, 5 items good, 1 item sufficient, and 2 items not very good. On effectiveness, from the analysis and discussion it was found that the learning media kahoot! quite effective in measuring understanding of the concepts of temperature and heat with a percentage of 67%, with several factors including students' understanding of concepts, accuracy in answering questions, maximizing the use of time, and stability of the internet network.